ANALISA HUBUNGAN BEBAN PAJAK PENGHASILAN TAHUN SEBELUMNYA TERHADAP AKTIVITAS MANAJEMEN LABA TAHUN BERJALAN DENGAN MENGGUNAKAN FIRM SIZE DAN LEVERAGE SEBAGAI VARIABEL KONTROL PADA PERUSAHAAN PROPERTY, REAL ESTATE DAN KONSTRUKSI BANGUNAN DI INDONESIA - Seliya Esther Sampul; Yulius Jogi Christiawan (Business Accounting Review, 2017)
This research aims to test influence of income tax expense of prior year on earnings management activities of current year of property, real estate and building contruction companies in Indonesia by using firm size and leverage as control variables. Samples of this research will be selected with purposive sampling method. Furthermore, this study will use 59 financial reports of property, real estate and building construction public companies that registered in Indonesia Stock Exchange from 2010 until 2015. The data will be tested by using multiple linear regression analysis. The results showed that income tax expense, firm size and leverage had effect on earnings management simultaneously. Partially variable income tax expense had negative effect on earnings management, variable firm size had no effect on earnings management and leverage had negative effect on earnings management.